2012
DOI: 10.1123/ijsnem.22.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplements for Improving Body Composition and Reducing Body Weight: Where Is the Evidence?

Abstract: Weight-loss supplements typically fall into 1 of 4 categories depending on their hypothesized mechanism of action: products that block the absorption of fat or carbohydrate, stimulants that increase thermogenesis, products that change metabolism and improve body composition, and products that suppress appetite or give a sense of fullness. Each category is reviewed, and an overview of the current science related to their effectiveness is presented. While some weight-loss supplements produce modest effects (<2 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 132 publications
(153 reference statements)
1
26
0
1
Order By: Relevance
“…A recent comprehensive overview of the wide range of supplements promoted for weight loss concluded that there was little evidence of benefit from most of them (Manore, 2012). Many of these products contain stimulants-most commonly caffeine, ephedra, synephrine, and related compounds-as active ingredients and are therefore likely to be associated with some adverse effects, especially when consumed in amounts greater than the recommended dose.…”
Section: Supplements For Optimization Of Physiquementioning
confidence: 99%
“…A recent comprehensive overview of the wide range of supplements promoted for weight loss concluded that there was little evidence of benefit from most of them (Manore, 2012). Many of these products contain stimulants-most commonly caffeine, ephedra, synephrine, and related compounds-as active ingredients and are therefore likely to be associated with some adverse effects, especially when consumed in amounts greater than the recommended dose.…”
Section: Supplements For Optimization Of Physiquementioning
confidence: 99%
“…Notably, this formula does not contain the stimulant Ma Huang ( Ephedra sinica ), which has significant safety concerns when used for weight loss at large doses [7]. We also conducted standard acute and sub-chronic toxicity studies in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Over the counter dietary supplements are widely used by individuals attempting to lose weight, but evidence supporting their efficacy is lacking. As reviewed by Manore in 2012 [7], most dietary supplements only result in less than 2 kilogram (2-3%) weight loss in adults. Certain imported dietary supplements have been found to be adulterated with prescription drugs, including amphetamines, benzodiazepines, and fluoxetine, which has led to an FDA warning against their use [8].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] These products were designed to promote thermogenesis and increase metabolism, suppress appetite, and/or slow the absorption of fats and carbohydrates. [2][3][4] However, due to lack of directly attributable adverse effects to p-synephrine and bitter orange extract, the safety of p-synephrine was frequently questioned, such as the potential cardiovascular hazards (strokes and cardiac arrhythmias). [32][33][34][35] In recent one or two years, Stohs et al specially did some studies on the risk of p-synephrine.…”
Section: Discussionmentioning
confidence: 99%